2016
DOI: 10.18276/frfu.2016.4.82/2-70
|View full text |Cite
|
Sign up to set email alerts
|

Household Finance Diagnosis in Major Polish Cities

Abstract: Streszczenie: Cel-Pokazanie sytuacji materialnej polskich gospodarstw domowych w największych miastach w Polsce na tle kraju, ze szczególnym uwzględnieniem takich obszarów zarządzania finansami osobistymi, jak uzyskiwanie dochodów i wydatkowanie oraz oszczędzanie i zadłużanie się. Metodologia badania-Prezentowane wyniki badań zostały pozyskane w ramach badań ankietowych przeprowadzonych w 7 największych miastach Polski, tj. w Warszawie, Krakowie, Łodzi, Wrocławiu, Poznaniu, Gdańsku, Szczecinie, w ramach realiz… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(2 citation statements)
references
References 4 publications
0
2
0
Order By: Relevance
“…It can be concluded that the savings rate also does not reflect the wealth of household members. Research conducted by Świecka and Musiał (2016) for households located in the largest cities in Poland, give rise to the conclusion that current income is not the main determinant of prosperity and there is no statistical correlation between income and savings. Thus, the level of income does not necessarily determine the level of savings in households (Świecka, Musiał, 2016).…”
Section: Study Resultsmentioning
confidence: 99%
“…It can be concluded that the savings rate also does not reflect the wealth of household members. Research conducted by Świecka and Musiał (2016) for households located in the largest cities in Poland, give rise to the conclusion that current income is not the main determinant of prosperity and there is no statistical correlation between income and savings. Thus, the level of income does not necessarily determine the level of savings in households (Świecka, Musiał, 2016).…”
Section: Study Resultsmentioning
confidence: 99%
“…On the other hand, the identification of household income diversification in Poland, carried out by Muszyńska (2006), to assess the level of dispersion of household income, showed that Polish households were significantly diversified in terms of income. According to the research included in the above article, the amount of income is affected by the fact that households belong to different economic and social groups and have Świecka and Musiał, 2014;Kramer, 2004. 101-115. http://dx.doi.org/10.17306/J.JARD.2021.01431 www.jard.edu.pl a varied number of members.…”
Section: Introductionmentioning
confidence: 99%